Partisipasi Mahasiswa Dalam Pengajaran Siswa Sekolah Dasar - Fitrainy, Cahaya Lunar; Dian Candra Dewi (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
The Teaching Campus Program (Program Kampus Mengajar) provides opportunities for students to participate in helping the learning process in elementary and junior high schools. Writing this article aims to describe student participation in teaching elementary school students. The activity was carried out by the Himpunan Mahasiswa Penerima Beasiswa (Himapeba) Universitas Widyagama Malang. The school that became the activity partner was the SDN 3 Gading Kembar, Jabung District, Malang Regency. Teaching activities are carried out for 2 weeks for 1st to 5th grades students. The implementation of the activity shows the enthusiasm of students in the learning process which can be seen in the interactions that occur during the activity